2021
DOI: 10.1002/vms3.455
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and rapid detection of Fasciola hepatica copro‐DNA in sheep using loop‐mediated isothermal amplification (LAMP) technique

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
13
0
3
Order By: Relevance
“…There was no cross-reactivity and the specificity of PCR and RPA was 100% ( 36 ). Besides, there was kappa agreement (0.72) among microscopic diagnostic tests, PCR and loop-mediated isothermal amplification (LAMP), based on IGS and examine on stool sheep samples, and the LAMP could be used in the field conditions of fascioliasis in animals ( 37 ). The results of another study showed that the subjects who were positive for ELISA, their stool and urine samples were 96% and 90% positive by nested PCR (use of ITS1 such as present study) respectively, and only 20% of samples was diagnosed by parasitology method ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was no cross-reactivity and the specificity of PCR and RPA was 100% ( 36 ). Besides, there was kappa agreement (0.72) among microscopic diagnostic tests, PCR and loop-mediated isothermal amplification (LAMP), based on IGS and examine on stool sheep samples, and the LAMP could be used in the field conditions of fascioliasis in animals ( 37 ). The results of another study showed that the subjects who were positive for ELISA, their stool and urine samples were 96% and 90% positive by nested PCR (use of ITS1 such as present study) respectively, and only 20% of samples was diagnosed by parasitology method ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Для подтверждения диагноза большинства трематодных инвазий используется микроскопия образцов стула пациента, так как метод является простым и доступным в выполнении, однако, позволяет выявить только инвазию средней и высокой интенсивности [12,16]. Большей чувствительностью и универсальностью при низкой интенсивности инвазии обладает метод седиментации [15,17,18]. Микроскопия образцов фекалий, мочи или дуоденального содержимого требует обеспечение лаборатории световым микроскопом и квалицированным опытным персоналом, что не всегда возможно в эндемичных очагах трематодозов.…”
Section: современные технологии микроскопииunclassified
“…К тому же визуализация результата тоже достаточно проста -колориметрическое изменение раствора наблюдается под ультрафиолетом. Схожие результаты были представлены в исследовании сравнения классических паразитологических исследований (прямой влажный препарат и метод концентрации), методов ПЦР и LAMP для диагностики F. hepatica в образцах фекалий овец [18]. Также LAMP-анализ позволяет избежать перекрестных реакций с другими видами.…”
Section: молекулярно-генетические методыunclassified
“…Molecular methods are available for F. hepatica detection in fecal samples, such as PCR, loop-mediated isothermal amplification (LAMP) and recombinase polymerase amplification (RPA). A nested-PCR based on fecal samples may detect the infection at two weeks post infection, while with the LAMP method, the detection time can be as early as one week post infection [ 29 , 30 ]. RPA may be used in areas with limited resources since it does not involve thermal cycler equipment or is dependent on trained personnel [ 31 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Other flukicides only active against adults include: albendazole, clorsulon, closantel, oxyclosantel, nitroxynil and rafoxanide [ 11 , 36 ]. However, resistance has already been reported for some of these [ 30 , 37 , 38 , 39 , 40 ]. To delay the onset of resistance, flukicidal drugs should be used strategically.…”
Section: Treatment and Resistance Towards Flukicidesmentioning
confidence: 99%